Estimasi Sintesis Protein Mikrobia Rumen Menggunakan Ekskresi Derivat Purin dalam Urin dengan Teknik Spot Sampling pada Kambing Bligon dan Kambing Kejobong - Dianestu Putra; Lies Mira Yusiati; Ristianto Utomo (Buletin Peternakan, 2016)
This study were aimed to determine the correlation between concentration of purine derivatives (PD) in spot sample with PD total excretion in Bligon and Kejobong goats and determine the appropriate sampling time, in order to predicting microbial protein synthesis in both breeds. Six male Bligon goats and six male Kejobong goats with age range from 8 to 14 months and body weight from 16 to 21 kg were placed in metabolism cages. Peanut straw and water were given to both groups of goats through ad libitum feeding and drinking. The study was done in 14 days for adaptation, 3 days for collection. Sample of feeds, feed residues, and feces were collected and then analyzed to determine dry matter and organic matter content. Spot urine and the total daily urine samples were also collected. Samples collection of spot sampling technique was run by taking the urine periodically with 3 hours intervals at 24 hours. Urine samples were analyzed for the content of creatinine and PD which includes allantoin, uric acid, xanthine, and hypoxanthine. Data were tested for the correlation between concentration of PD spot urine sample with total PD daily excretion. It is known that the concentration of PD and creatinine (µmol/L) for Bligon were 1,418.40 and 202.85 respectively, while for Kejobong were 1,547.40 and 219.68 respectively. Total excretion of PD, allantoin, uric acid, xanthyne and hypoxanthine and creatinine (µmol/W0,75/day) for Bligon were 114.14, 95.86, 17.31, 0.97, and 16.40 respectively, with microbial protein synthesis efficiency was 4.61 g N/kg degraded of organic matter in rumen (DOMR). Total excretion of PD allantoin, uric acid, xanthyne and hypoxanthine and creatinine (µmol/W0,75/day) for Kejobong were 180.18, 158.17, 20.60, 1.40, and 24.87 respectively, with microbial protein synthesis efficiency was 6.90 g N/kg DOMR. Based on this study also known that the best time for spot sampling to determine the total excretion of PD in Bligon was in the range time of 11.00 am to 2.00 pm, with equation Y=1.474X+48.81, while Kejobong goat in the range of 2.00 to 5.00 pm, with equation Y=2.678X+5.692.